The Analysis of Development Disparities Inter Districts/ City in Special Region of Yogyakarta (DIY) Province 2003-2013 - Anisa Nurpita; Aulia Agni Nastiti (Magister Administrasi Publik, 2016)
One of the objectives of regional economic development is to increase the economic sector, in which the increasing of economics sector will be beneficial for society. This indicator is important to recognize the condition of the economy in particular region in given period indicated by GDRP (Gross Domestic Regional Product) data of the region or area. Since the enactment of the autonomy then the local Government has bigger role in managing regional economic potential that exists in its territory. Economic growth is one of indicators that affect economic development. Economic development in substance aims to increase public welfare. Yogyakarta province is one of cities on the island of Java with the level of GDRP that keeps increasing each year since 2003 until 2013.In the development process there are also regions that have abundant of natural resources but lacking in human resources, and yet there are also regions that are otherwise lacking in terms of natural resources however have abundant in human resources, both in quality and quantity. This situation then leads to the distinction in development that resulted in the economic growth and disparities welfare in each region. The research also aims to identify the patterns of economic growth according to Klassen Typology and describe the level of regional disparities between districts/cities in Special Region of Yogyakarta (DIY) Province. The methods of analysis used covers analysis of the Klassen Typology, inequality Williamson Index, and inequality Theil Entropy Index. The results showed classifications according to Klassen Typology, Yogyakarta is concluded in the category of advanced and fast growing area. The index disparities show a pattern of increasing. This implies that development in district / cities in Special Region of Yogyakarta (DIY) Province are increasingly uneven.